Traditional Conflict Medicine? Lessons for Putting Mali and Other African Countries on the Road to Peace - Peter J. Schraeder (Nordic Journal of African Studies, 2011)
The primary thesis of this article is that Mali’s success during the 1990s in resolving a sixyear conflict between the Malian government and a northern-based insurgency among the Tuareg ethnic group was primarily due to the emergence of democratically elected elites who sought recourse to traditional mediation practices that are derivative of Mali’s precolonial independence era; what one group of Africanists has referred to as “traditional conflict medicine.” The analysis focuses on traditional Malian mediation practices that have served as the centerpiece of a veritable “culture of peace” and that continue to pervade contemporary Malian society. It is argued that recourse to these practices will be critical to resolving Mali’s spring 2012 crisis that included the return of heavily armed insurgents to northern Mali amidst civil war in Libya, a military coup d’etat that ended two decades of democratic rule, and the secession of northern Mali as the independent country of Azawad. A concluding section assesses the practical lessons from Mali’s experience during the 1990s that potentially can be of use to observers interested in facilitating the resolution of Mali’s 2012 conflict as well as those in other parts of the African continent.